Reproducibility and reaction time of swallowing as markers of dysphagia in parkinsonian syndromes. Issue 9 (September 2020) - Cosentino, Giuseppe; Tassorelli, Cristina; Prunetti, Paolo; Todisco, Massimiliano; De Icco, Roberto; Avenali, Micol; Minafra, Brigida; Zangaglia, Roberta; Valentino, Francesca; Pacchetti, Claudio; Bertino, Giulia; Mauramati, Simone; et al.
Highlights: Swallowing reproducibility reduces in dysphagic patients with parkinsonian syndromes Swallowing reaction time increases in parkinsonian syndromes with dysphagia Reproducibility of the oral phase and reaction time of swallowing correlate with dysphagia severity in parkinsonian syndromes. The above-mentioned swallowing abnormalities correlate with dysphagia severity. Abstract: Objective: To investigate reproducibility and reaction time of oropharyngeal swallowing in patients with Parkinson's disease (PD) and atypical parkinsonisms (APs). Methods: We enrolled 19 patients with PD, 30 with APs, and 20 healthy subjects. Presence and severity of dysphagia were assessed with clinical and fiberoptic endoscopic evaluations of swallowing. Reproducibility of the oral and pharyngeal phases of swallowing were respectively assessed by calculating the 'similarity index' of the electromyography activity of the submental/suprahyoid muscles and of the laryngeal-pharyngeal mechanogram during consecutive swallows. These were performed both 'on command' and spontaneously. The swallowing reaction time was also recorded. Results: Reproducibility of the oral phase of swallowing was reduced in patients with dysphagia, mainly when swallowing 'on command'. Swallowing reaction time was prolonged in dysphagic patients. These electrophysiological parameters did not vary among different parkinsonian syndromes and correlated with dysphagia severity. Conclusions: Increased variability of oral swallowing automatisms and abnormal sensorimotor integration may be of relevance for the pathophysiology of dysphagia in parkinsonian syndromes. Significance: The electrophysiological assessment represents a valuable tool to investigate swallowing alterations in parkinsonian syndromes. It may also provide useful insights into clinical severity and pathophysiology of dysphagia, giving clues for the choice of the best therapeutic approach.